Limit behavior of the distribution of the ruin moment of a modified risk process - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For modified risk process with instantaneous reflection at the point $B > 0$ under which the considered process$$ζ(t) = ζ_{B, μ}(t),\; ζ(0) = u,\; 0 ≤ u ≤ B,$$returns in the initial state $u$, we investigate the limit behavior of generating function of the first ruin moment as $u → B$ and $B → ∞$.